Strategi Pembelajaran Metodologi Penelitian Bahasa Arab di Era Pandemi - Luhuringbudi, Teguh (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
This research paper aims to analyze innovative learning strategies for Arabic language research methodology in the pandemic era, which requires students to be able to write Student Article Plans (RAM) based on the offer of Selected Journal Article Titles (AJP) presented by the course lecturer. This research paper is a "qualitative research" as well as a classroom action research that combines the dominance of "literature research" and "field research". The method used in this research paper is "Learning by Doing and Works in Learning and Teaching" to analyze the progressiveness and evaluate both. This paper succeeded in discovering the ability of eleven students to write RAM from the title, introduction subchapter to the method subchapter, so that they became semi-final papers. Another finding in this research paper is the first experience of students in writing RAM-based papers, which are compiled and printed in the form of a compilation book to evaluate their academic performance in the Arabic Language Research Methodology course; and academic results as materials for accreditation of majors or study programs.